Specializing in Politics: Effects of Specialization, Social Capital, and Human Capital on Corporate Lobbying. Issue 5 (20th October 2022) - Brown, Lee Warren; Harris, Christopher M.
ABSTRACT: Corporate lobbyists play a vital role in the Corporate Political Activity process. They act as a mediator between corporations and politicians when firms engage in lobbying activities. Firms value professional lobbyists for their connections in Washington and their knowledge of the political process. While previous Corporate Political Activity research on lobbying has focused primarily on the amount of money firms spend on lobbying, including antecedents of lobbying and outcomes, very little research has examined lobbyists' individual differences and how those influence important outcomes. In this paper, we examine how lobbyists' specialization and experience as both a lobbyist and a former politician can influence the number of bills lobbied on passed into law. Using a sample of corporate lobbyists who were hired by S&P 500 firms, we look at 8, 630 lobbyist's careers from 2005–2016. We find that lobbyists lower in specialization are more likely to lobby on bills which are eventually passed into law than highly specialized lobbyists. We also find that social capital moderates the relationship between specialization and lobbying effectiveness. These results suggest that while corporate political activity spending is important, both scholars and firms should also understand who firms are hiring to lobby for them and how differences in lobbyist specialization might influence firm effectiveness in the nonmarket arena.